Smaller left ventricular end-systolic diameter and lower ejection fraction at baseline associated with greater ejection fraction improvement after revascularization among patients with left ventricular dysfunction - Wang, Shaoping; Lyu, Yi; Cheng, Shujuan; Zhang, Yuchao; Gu, Xiaoyan; Gong, Ming; Liu, Jinghua (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To investigate the predictive roles of preoperative left ventricular (LV) size and ejection fraction (EF) in EF improvement and outcome following revascularization in patients with coronary artery disease (CAD) and LV dysfunction. Background: Revascularization may improve EF and long-term outcomes of patients with LV dysfunction. However, the determinants of EF improvement have not yet been investigated comprehensively. Meathods: Patients with EF measurements before and 3 months after revascularization were enrolled in a cohort study (No. ChiCTR2100044378). All patients had baseline EF ≤40%. EF improvement was defined as absolute increase in EF >5%. According to LV end-systolic diameter (LVESD) (severely enlarged or not) and EF (≤35% or of 36% to 40%) at baseline, patients were categorized into 4 groups. Results: A total of 939 patients were identified. 549 (58.5%) had EF improved. Both LVESD (odds ratio [OR] per 1mm decrease, 1.05; 95% CI, 1.04-1.07; P<.001) and EF (OR per 1% decrease, 1.06; 95% CI, 1.03-1.10; P<.001) at baseline were predictive of EF improvement after revascularization. Patients with LVESD not severely enlarged and EF ≤35% had higher odds of being in the EF improved group in comparison with other 3 groups both in unadjusted and adjusted analysis (all P<.001). The median follow-up time was 3.5 years. Patients with LVESD not severely enlarged and EF ≤35% had significantly lower risk of all-cause death in comparison with patients with LVESD severely enlarged and EF ≤35% (hazard ratio [HR], 2.73; 95% CI, 1.28-5.82; P=.009), and tended to have lower risk in comparison with patients with LVESD severely enlarged and EF of 36% to 40% (HR, 2.00; 95% CI, 0.93-4.27; P=.074). Conclusions: Among CAD patients with reduced EF (≤40%) who underwent revascularization, smaller preoperative LVESD and lower EF had greatest potential to have EF improvement and better outcome. Our findings imply the indication for revascularization in patients with LV dysfunction who presented with lower EF but smaller LV size.